2009
DOI: 10.1590/s0101-20612009000200028
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da carne de cordeiros confinados recebendo diferentes relações de volumoso: concentrado na dieta

Abstract: O aumento da oferta de carne ovina no Brasil está associado à melhoria dos sistemas de produção, visando atender à grande demanda do mercado consumidor. Principalmente nos grandes centros urbanos, muitas pessoas buscam adquirir produtos cárneos de maior qualidade provenientes principalmente de animais jovens terminados em confinamento. Porém, a ovinocultura de corte em sistemas intensivos de produção, encontra obstáculos em relação ao custo da dieta, um dos aspectos mais importantes na produção de carne (YAMAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
3
6
0
13
Order By: Relevance
“…Mean values found for shear forced in the present study were higher than those found by Pinheiro et al (2009) in Ile de France×Santa Inês lambs (1.02 kgf) slaughtered at 32-kg liveweight and similar to the mean value found by working with Hampshire Down lambs slaughtered at 31 kg (3.3 kgf). All samples in the present study may be considered tender as values were below 4.6 kg, considered as a meat of an acceptable tenderness (Miller et al 2001).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Mean values found for shear forced in the present study were higher than those found by Pinheiro et al (2009) in Ile de France×Santa Inês lambs (1.02 kgf) slaughtered at 32-kg liveweight and similar to the mean value found by working with Hampshire Down lambs slaughtered at 31 kg (3.3 kgf). All samples in the present study may be considered tender as values were below 4.6 kg, considered as a meat of an acceptable tenderness (Miller et al 2001).…”
Section: Discussionsupporting
confidence: 78%
“…The lack of significant differences between meat from animals slaughtered at 35 and 45 kg in the Santa Ines group, may be related to the greater fat content in the latter. According to Pinheiro et al (2009) meat tenderness is an important quality as more tender meats have higher commercial value.…”
Section: Discussionmentioning
confidence: 99%
“…Não foram encontradas diferenças (P>0,05) das dietas sobre a força de cisalhamento da carne dos cortes pesquisados (Tabela 7). Pinheiro et al (2009) O tecido conectivo que confere resistência ao músculo e aos tendões é constituído principalmente pelo colágeno. Segundo Cranwell et al (1996), o colágeno total é relativamente constante nos animais nas diferentes idades, mas, com o aumento da idade, as ligações tornam-se mais resistentes e estáveis, conferindo à carne maior resistência ao corte.…”
Section: Resultsunclassified
“…Thus, studies that evaluate the roughage:concentrate ratios in the diet are important for the establishment of the most appropriate nutritional plan for the production system. However, such data are almost inexistent in the scientific literature, especially on females, which present great importance in the current productive scenario (Pinheiro et al, 2009).…”
Section: Introductionmentioning
confidence: 99%